Nursing Care of a Patient Diagnosed with Thalassemia Major According to Gordon’s Functional Health Patterns Model: A Case Report - Gülbeyaz Baran Durmaz; Metin Suiçmez (Artuklu Health)
Introduction: Thalassemia is a subtype of Mediterranean anemia, a genetic disease, and is caused by genetic defects during the synthesis of the hemoglobin molecule. It is closely associated with errors in the α and β globin synthesis genes. This genetic disorder can cause various problems in basic health areas.Case Report: B.A., a 15-year-old girl, was diagnosed with thalassemia and type 1 diabetes, resulting in frequent hospitalizations due to fatigue, infections, and blood sugar management issues. She also faced stress, emotional instability, and a decline in her quality of life. A comprehensive assessment using Gordon’s Functional Health Patterns Model identified nursing diagnoses by NANDA-I (North American Nursing Diagnosis Association - International). B.A.’s family, with limited knowledge about her conditions, actively participated in educational programs. Interventions included stress management, patient education, family training, psychosocial support, and physical rehabilitation.Conclusion: Results of these interventions lead to improvements in B.A.’s stress, self-esteem, sleep, attention, and physical activity. This case highlights the effectiveness of Gordon’s Model in managing thalassemia and diabetes, positively impacting B.A.’s quality of life. It is recommended that future qualitative and quantitative studies or case presentations, be conducted with larger sample sizes.